Murillo's miracle of Saint John of God - María Teresa Miralles Sangro; Marta Durán Escribano (Universidad de Alicante, 2012)
An iconographic analysis will be made of the interesting painting by Murillo (1617-1682), San Juan de Dios (Saint John of God), from the Holy Charity Hospital in Seville. This painting has been restored and was exhibited at the Prado Museum between January and March 2006. The analysis will make it possible to: 1. Become acquainted with the social and historical context leading to the portrayal of a person who became famous for his special devotion towards looking after other people. 2. Show art as a historical source; rather than a mere technique, it should be considered as the language of a whole age, and not even of one person. 3. Explore the issues of "views on health, knowledge on healthcare and healthcare providers" at the time the painting was made in the Seville of its time. 4. Analyze the discourse and its contents. An iconographic analysis of Murillo's San Juan de Dios will make it possible to discover what lies hidden beyond the representation, and will explain the choice of Saint John of God's fall. An attempt has been made to re-read our history, in the awareness that all human events can be seen from a different point of view. In spite of the difficulty to reach a conclusion to our study, it is our belief that some humanist issues on nursing can be detected, in an age heavily influenced by Renaissance humanism, as expressed in the bonds between the nurse and the patient.